PENGARUH BERPIKIR POSITIF DAN BERPIKIR KREATIF TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Sasti, Andi Ika Prasasti Abrar; Yuliany, Nur; Hardiana (Program Studi Tadris Matematika dan Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Universitas Islam Negeri (UIN) Datokarama Palu, 2023)
The purpose of this study is to evaluate the impact of students' positive and creative thinking abilities on their learning outcomes. This research uses a quantitative approach with an ex post facto research design. The sample consists of 54 students selected from a population of 117 students at SMP Negeri 3 Camba using purposive random sampling technique. Data collection is conducted using a questionnaire to assess positive thinking ability, a test to assess creative thinking ability, and documentation of student learning outcomes. The data obtained is analyzed using multiple regression tests after fulfilling the prerequisite tests. The results of the study indicate that the students' positive and creative thinking abilities are in the moderate category with an average of 73.59 and 77.78, respectively. In addition, the students' mathematics learning outcomes are in the moderate category with an average of 73.93. Based on the hypothesis testing results, students' positive and creative thinking abilities have a significant effect on mathematics learning outcomes for eighth grade students at SMPN 3 Camba, both partially and simultaneously